Abdominal Fat and Sarcopenia in Women Significantly Alter Osteoblasts Homeostasis In Vitro by a WNT/β-Catenin Dependent Mechanism. (20th May 2014) - Wannenes, Francesca; Papa, Vincenza; Greco, Emanuela A.; Fornari, Rachele; Marocco, Chiara; Baldari, Carlo; Di Luigi, Luigi; Emerenziani, Gian Pietro; Poggiogalle, Eleonora; Guidetti, Laura; Donini, Lorenzo M.; Lenzi, Andrea; et al.
Abstract : Obesity and sarcopenia have been associated with mineral metabolism derangement and low bone mineral density (BMD). We investigated whether imbalance of serum factors in obese or obese sarcopenic patients could affect bone cell activity in vitro . To evaluate and characterize potential cellular and molecular changes of human osteoblasts, cells were exposed to sera of four groups of patients: (1) affected by obesity with normal BMD (O), (2) affected by obesity with low BMD (OO), (3) affected by obesity and sarcopenia (OS), and (4) affected by obesity, sarcopenia, and low BMD (OOS) as compared to subjects with normal body weight and normal BMD (CTL). Patients were previously investigated and characterized for body composition, biochemical and bone turnover markers. Then, sera of different groups of patients were used to incubate human osteoblasts and evaluate potential alterations in cell homeostasis. Exposure to OO, OS, and OOS sera significantly reduced alkaline phosphatase, osteopontin, and BMP4 expression compared to cells exposed to O and CTL, indicating a detrimental effect on osteoblast differentiation. Interestingly, sera of all groups of patients induced intracellular alteration in Wnt/ β -catenin molecular pathway, as demonstrated by the significant alteration of specific target genes expression and by altered β -catenin cellular compartmentalization and GSK3 β phosphorylation. In conclusion our results show for the first time that sera of obese subjects with low bone mineral density and sarcopenia significantly alter osteoblasts homeostasis in vitro, indicating potential detrimental effects of trunk fat on bone formation and skeletal homeostasis.